Homework Help

If f''(x) = 2*x*f'(x), and f(x) = x^(n) what is n.

user profile pic

torrip996 | Student, Grade 10 | Salutatorian

Posted September 11, 2013 at 4:27 PM via web

dislike 0 like

If f''(x) = 2*x*f'(x), and f(x) = x^(n) what is n.

2 Answers | Add Yours

user profile pic

aruv | High School Teacher | Valedictorian

Posted September 28, 2013 at 5:17 AM (Answer #2)

dislike 0 like

`f''(x)=2x xx f'(x)`  and  `f(x)=x^n`

Consider

`f(x)=x^n`       (i)

Differentiate (i) w.r.t. x, then

`f'(x)=nx^(n-1)`

`f''(x)=n(n-1)x^(n-2)`

Substitute `f'(x) and f''(x)`  in given equation,

`n(n-1)x^(n-2)=2xnx^(n-1)`

`n(n-1)x^(n-2)-2xnx^(n-1)=0`

`nx^(n-2)(n-1-2x^2)=0`

So either `nx^(n-2)=0`  or `n-1-2x^2=0.`

`If `  `nx^(n-2)=0`

`=> n=0`  or x=0

If `n-1-2x^2=0`  then n will variable as x is independent variable. So this case not possible.

Thus only posible cases are either n=0 or x=0.

user profile pic

science2014 | (Level 1) Assistant Educator

Posted June 30, 2014 at 5:44 PM (Answer #3)

dislike 0 like

f(x) = x^(n)

Hence, f'(x) = d/dx [x^(n)] = n x^(n-1)   ....  (1)

Hence, f''(x) = d/dx [f'(x)] = d/dx [n x^(n-1)] = n (n - 1) x^(n-2)  .... (2)

As f''(x) = 2*x*f'(x)

So plugging in the values from (1) and (2) we get,

n (n - 1) x^(n-2) = 2*x*n x^(n-1)

or (n - 1) x^(n-2) = 2*x* x^(n-1)      assuming n ≠ 0

or (n -1) x^(n-2) = 2* x^(n-1+1)

or (n-1) x^(n-2) = 2*x^(n)

or (n-1)/2 = x^(n) / x^(n-2)

or (n-1)/2 = x^(n - n + 2)

or n-1 = 2*x^2

or n = 1 + 2*x^2

If n is not a variable function of x, we are left with the other option of n = 0

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes